Characterization and Properties of Treated Oil Palm Empty Fruit Bunch Regenerated Cellulose Biocomposite Films with Butyl Methacrylate Using Ionic Liquid. Issue 2 (22nd January 2017) - Zailuddin, Nur Liyana Izyan; Husseinsyah, Salmah; Hahary, Farah Norain; Ismail, Hanafi
ABSTRACT: Regenerated cellulose biocomposite films from oil palm empty fruit bunch and microcrystalline cellulose were prepared using N, N -dimethylacetamide and lithium chloride. The effects of oil palm empty fruit bunch contents and butyl methacrylate on properties of regenerated cellulose biocomposite films were investigated. At 2 wt% of untreated oil palm empty fruit bunch content showed highest crystallinity index, tensile strength, modulus of elasticity, and thermal stability but lower elongation at break than other oil palm empty fruit bunch content. The treated regenerated cellulose biocomposite films with butyl methacrylate showed better tensile strength, modulus of elasticity, thermal stability, and crystallinity index while Fourier transform infrared spectroscopy study showed interaction between cellulose and butyl methacrylate. GRAPHICAL ABSTRACT: